Tau pathology, neuroinflammation and adaptive immune cells in human primary tauopathies. (December 2021) - Hartnell, Iain James; Graffeuil, Manon; Mason, Luke; Marwaha, Pavan; Woodhouse, Declan; Jasper, William; Blum, David; Nicoll, James AR; Dorothee, Guillaume; Boche, Delphine
Abstract: Background: Primary tauopathies are neurodegenerative disorders that result from the accumulation of aggregated tau in the brain. Frontotemporal lobar degeneration with tau (FTLD‐tau) is a tauopathy that underlies ∼50% of cases of frontotemporal dementia (FTD). The discovery of genetic risk variants related to innate/adaptive immunity have highlighted a potential role for neuroinflammation in FTLD. Furthermore, studies have shown microglial and astrocyte activation together with T cell infiltration in the brain of THY‐Tau22 tauopathy mice. Methods: To study the relationship between tau and neuroinflammation we obtained FFPE brain tissue from 12 FTLD‐MAPT, 33 Pick's Disease (PiD), 45 Progressive Supranuclear Palsy (PSP) patients and 55 controls, via Brain UK. Using immunohistochemistry, we assessed tau pathology using antibodies 8 epitopes of tau with phosphorylation are different site. The immunophenotype of microglia were assessed with phenotypic markers and their morphology (ramified, reactive, ameboid) was analysed using Iba1. Astrocytic phenotype and T cell infiltration exploration is currently ongoing. Results: Tau epitopes AT8, AT100, PHF1, CP13 and Tau‐2 were increased in PiD, PSP and FTLD‐MAPT compared to controls, with expression levels significantly correlated between tau epitopes. Others are currently under analysis. Microglial markers Iba1, CD68, HLA‐DR and CD64 showed no difference between groups. However, CD16 was significantly increased in FTLD‐MAPT vs. control (p = 0.03) and correlations between tau and microglial markers (except with Iba1) were detected between disease groups. Morphological assessment revealed that ameboid microglia were the highest represented population in PiD and FTLD‐MAPT (p<0.0001 and p<0.0001, respectively); while reactive microglia were the most abundant population in PSP (p<0.0001). Preliminary observation of T cell staining confirms their recruitment in FTLD‐tau. Conclusion: These findings support the involvement of microglia in FTLD‐tau. Additional immuno‐phenotyping is necessary for further defining their role as well as T cell involvement in the disease pathogenesis.